Universal Design for Learning and attention to diversity in basic education students (Revista Innova Educación, 2023)
In today's society, educating and providing attention to student diversity is presented as a great challenge. The objective of this article was to analyze how the Universal Learning Design (DUA) affects attention to diversity. The methodology used was based on a qualitative-quantitative approach, with a descriptive and exploratory investigation, the methods used were analysis and synthesis to delve into the object of study using survey and interview techniques. The results denote that, those teachers have adequate perceptions to apply the principles of the UDL, also indicate that the lack of training in inclusive tools becomes a great limitation; On the other hand, the experts state that changes are required in terms of planning and methodologies, actions necessary for the application of the DUA. It is concluded that teachers use the three principles of the DUA: representation, motivation, action and expression; being these relevant to achieve significant learning and transform education, as well as in the construction of innovative strategies for the achievement of objectives, which allow the development of motivation, sense of responsibility and autonomy. They also agree that there is a need for training in communication systems such as Braille and sign language, as well as access to computer and electronic materials with their respective support software for attention to diversity.
Keywords: diversity; UDL; didactic strategies; educational inclusion